2021
DOI: 10.3390/ijerph18136730
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Predictors of University Students’ Wellbeing during the COVID-19 Pandemic—A Data-Driven Approach

Abstract: Background: The COVID-19 pandemic has posed risks to public mental health worldwide. University students, who are already recognised as a vulnerable population, are at elevated risk of mental health issues given COVID-19-related disruptions to higher education. To assist universities in effectively allocating resources to the launch of targeted, population-level interventions, the current study aimed to uncover predictors of university students’ psychological wellbeing during the pandemic via a data-driven app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 45 publications
(55 reference statements)
1
44
1
1
Order By: Relevance
“…For example, Olmos-Gómez [54] found frustration, malaise, and decreased resilience to be the main problems in students who either did not engage in physical activity or frequently watched pandemicrelated news [55]. Liu et al [56] reached similar conclusions regarding the importance of physical health, emotional support, and resilience as factors promoting psychological well-being among students. Similarly, Eva et al [49] found that students who were able to regulate their emotions during the confinement obtained greater personal satisfaction and better academic results.…”
Section: Resilience and Covidmentioning
confidence: 93%
“…For example, Olmos-Gómez [54] found frustration, malaise, and decreased resilience to be the main problems in students who either did not engage in physical activity or frequently watched pandemicrelated news [55]. Liu et al [56] reached similar conclusions regarding the importance of physical health, emotional support, and resilience as factors promoting psychological well-being among students. Similarly, Eva et al [49] found that students who were able to regulate their emotions during the confinement obtained greater personal satisfaction and better academic results.…”
Section: Resilience and Covidmentioning
confidence: 93%
“…Additionally, the risk of depression symptoms was three times higher between students who had confirmed and suspected COVID-19 cases among relatives [14]. Australian university students reported 66.3% poorer well-being overall during the pandemic [15].…”
Section: Introductionmentioning
confidence: 94%
“…The PHQ-9 scores can range between 0 to 27 because each item of PHQ-9 can be scored from 0 (not at all) to 3 (nearly every day). The PHQ-9 rates Minimal depression (0-4), Mild depression (5-9), Moderate depression (10-14), Moderately severe depression (15)(16)(17)(18)(19), and Severe depression (20)(21)(22)(23)(24)(25)(26)(27). It is designed to assess depression based on the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM-IV) criteria (American Psychiatric Association, 2000).…”
Section: Mental Health Measuresmentioning
confidence: 99%
See 2 more Smart Citations